Biocerâmica de fosfatos de cálcio nano-estruturado micro-macro porosa em grânulos em defeito crítico em rádio de coelhos (Oryctolagus cuniculus) - Omar Leonardo Aristizabal Paez (2013)
The objectives of this study were to determine the characteristics and structural properties of bioceramic calcium phosphate nano-structured micro macro porous granules of slow absorption and moderated by scanning electron microscopy (SEM) and evaluate its effect on critical defects in experimental rabbits radio by clinical, radiographic, histologic and densitometric (DMO). The analysis on the SEM showed up to 10 um micropores and macropores of diameter greater than 100 micrometers. We used 70 New Zealand rabbits, young adults, males in which we performed a critical defect in both radios. The members formed groups:GI, bioceramic slow, GII, GIII and bioceramic moderate, negative control. Radiological assessments were made before surgery, immediately after the eighth, 15, 30, 45, 60, 90 and 120 days followed by euthanasia by anesthetic overdose at the end of each time. The radios were harvested for evaluation of densitometry, histological and scanning electron microscopy. The SEM was taken at 60, 90 and 120 days. It was observed radiographically increased density of the implant at eight and 15 days with a gradual decrease until reaching a radiopacity similar to the adjacent bone tissue. Histologically there was formation of vascular network between the pores of both bioceramics from 8 days training of primary and trabecular bone at 30 days, primary osteons and compact bone at 120 days, filling the entire defect, the presence of osteons Secondary and Haversian systems evident. The BMD increased up to 45 days in groups I and II, with a significant difference between the treated and control groups throughout the study period. Both bioceramics allow invasion and cell growth and promotes regeneration of bone, constituting a suitable implant for filling critical defects.